Analisis Pengaruh Pertumbuhan Populasi Terhadap Kebutuhan Perumahan di Kota Metropolitan Surabaya Tahun 2009-2024 - Kaprilia Anggraini; Hartiningsih Astuti; Khalid Fauzi Aziz (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study analyzes the effect of population growth on housing demand in the Metropolitan City of Surabaya for the period 2009-2024, where rapid population growth due to high birth rates has caused a housing shortage of more than 400,000 units. The main objective is to identify the partial and simultaneous impacts of birth rates, deaths, and urbanization on housing demand to support sustainable planning. A quantitative correlational approach is applied through multiple linear regression with Eviews 12 software, using secondary data from the Central Statistics Agency and the Surabaya Population Office, after fulfilling classical assumptions such as normality, heteroscedasticity, autocorrelation, and multicollinearity. The results show that the birth rate has a significant positive effect on housing demand, while the death rate and urbanization have no significant effect, with the independent variables only explaining 17.9% of the variation in housing demand. The main conclusion emphasizes the need for a housing strategy that is responsive to high fertility dynamics, as well as comprehensive policy recommendations for local governments to reduce the deficit of adequate housing amidst rapid urbanization.